New Furanocembranoids from Briareum violaceum - Huang, Pin-Chang (Mar Drugs, 2019)
Three new furanocembranoids—briaviodiol F (1) and briaviotriols A (2) and B (3)—along with a known analogue, briaviodiol A (4), were obtained from a cultured-type octocoral Briareum violaceum. The structures of cembranoids 1–3 were elucidated by using spectroscopic methods. In vitro study demonstrated that compounds 2 and 4 exerted inhibition effects on inducible nitric oxide synthase (iNOS) release from RAW 264.7, a macrophage cell line that originated from a mouse monocyte macrophage, stimulated with lipopolysaccharides.